Model Pembelajaran Konstruktivisme untuk Meningkatkan Kemampuan Pemahaman dan Komunikasi Matematika Siswa Sekolah Dasar - Roni Rodiyana; Wina Dwi Puspitasari (International Consortium of Education and Culture Research Studies, 2019)
One effort that can be done in addressing the low ability of mathematical understanding and communication, namely with constructivism learning models that emphasize students to construct their own knowledge. This research is an experimental study in Class IV of Cijati Elementary School and First District of Majalengka with a pretest and posttest research design given to the experimental group and the control group. The instruments used were tests of mathematical comprehension and communication skills, student attitude scales, teacher response questionnaires, and the observation format of student learning activities. The main objective of this study is to examine the mathematical comprehension and communication skills of elementary students who learn with constructivism learning and those who learn as usual. Data analysis was carried out quantitatively and qualitatively. Based on the results of the final test analysis, it was found that students' mathematical understanding and communication skills learning with the constructivism learning model were better than students who studied with ordinary learning. Student learning outcomes in the experimental group were at a level close enough to good and the learning outcomes control group was still at a lesser level. While qualitative analysis found that student learning activities in constructivism learning models are good. Students and teachers show a positive attitude towards this learning.